Analisis dan Perancangan Sistem Informasi Seleksi Karyawan Baru pada PT.Erafone Artha Retailindo Cabang Pekanbaru - Arribe, Edo; Damila, Miesie Sasikirana; Rezeki, Rezeki; Afrida, Ayuni; Putra, Rachel Pramana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Efficient and organized employee recruitment management is very important for the success of a company. In this digital era, web-based technology offers a great opportunity to improve the recruitment process by reducing time, costs and increasing the quality of prospective employees. This study aims to analyze and design an innovative and easy-to-use web-based recruitment system for the company PT ERAFONE ARTHA RETAILINDO to increase efficiency and accuracy in the recruitment process. The research method we use is waterfall and interviews with HR managers and the company's recruitment team to understand the process. current recruitment. We also carry out document analysis, such as historical data on previous recruitment and the recruitment platform used. The results of the system implementation show a significant increase in the response time of the recruitment process and the quality of candidates invited to further selection stages. The HR team also reported reduced workload and increased productivity due to the efficiency of the new recruitment system Keywords: Information systems, recruiting employees, system design, HR, waterfall